La "Stadtschrumpfung" ou "rétrécissement urbain" en Allemagne : un champ de recherche émergent - Daniel Florentin (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
Over the last decade, the concept of "Stadtschrumpfung" (urban decline) has become a crucial factor in German urban studies. It covers all the negative dynamics within the demographic, economic and social aspects of urban areas and especially of the German "new Länder". This article will offer a thematic review of the concept in German academic literature. Three main themes are to be analysed: the preconditions leading to the debate on urban decline, the analysis of the factors and symptoms of decline by German researchers, and the assessment of urban policies implemented to cope with the problem. We will eventually consider the contributions of the German debate and its criticisms of the dominant growth paradigm relating to urban studies and policies.